Poul Anderson and the American Alliterative Revival. Issue 2 (1st June 2021) - Wise, Dennis Wilson
Abstract : Although Poul Anderson is best known for his prose, he dabbled in poetry all his life, and his historical interests led him to become a major—if unacknowledged— contributor to the twentieth-century alliterative revival. This revival, most often associated with British poets such as W. H. Auden, J. R. R. Tolkien, and C. S. Lewis, attempted to adapt medieval Germanic alliterative meter into modern English. Yet Anderson, a firmly libertarian Enlightenment-style writer, imbued his alliterative poetry with a rationalistic spirit that implicitly accepted (with appropriate qualifications) a narrative of historical progress. This article analyzes the alliterative verse that Anderson wrote and uncovers how the demands of the pulp market shaped what poetry he could produce.